(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Chronic renal failure is a complex of symptoms caused by the death of nephron cells and causes many complications due to irreversible changes in the mass of nephrons in motion due to primary and secondary kidney diseases. Chronic kidney diseases are one of the most acute problems in Uzbekistan, as well as throughout the world, and are among the diseases of social significance with a high mortality rate and high financial costs. This is mainly common among the working population.